ISLAM ASIA TENGGARA KONTEMPORER ABAD KE-21: STUDI PENDIDIKAN SEJARAH ATAS KONFLIK BERNUANSA AGAMA DI THAILAND - Mardhiah; Fuji Attariq Unsha; Muhammad Al-Mustafa; Muhammad Jafar; Nukman Hasibuan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the dynamics of contemporary Southeast Asian Islam in the 21st century through a historical education study of religiously charged conflicts in Southern Thailand rooted in ethnic and religious pluralism and state power relations. This study aims to analyze the Patani conflict as a product of a long history of marginalization and homogenous nationalist policies, and to position it as reflective material in the study of Southeast Asian Islamic history. The method used is qualitative research with library research and a descriptive-analytical approach, through a search of historical literature, state policies, and contemporary studies using reflexive thematic analysis. The results of the discussion indicate that the conflict in Southern Thailand cannot be reduced to a mere issue of radicalism, but is closely related to the loss of sovereignty of the Patani Sultanate, cultural and educational assimilation policies, and the structural marginalization of the Malay Muslim community of Patani. The research findings confirm that Islam functions as a social identity, collective memory, and symbol of resistance to state domination, while education, both as an instrument of the state and a space for cultural resistance, plays a key role in shaping the conflict. The implications of this research demonstrate the importance of a critical, multi-perspective, and empathetic approach to history education to build historical awareness, strengthen multicultural understanding, and promote a narrative of peace in contemporary Southeast Asian Islamic studies.